Basics of Legal Authority Forest Management In Indonesia - Ramlani Lina Sinaulan (The Southeast Asia Law Journal, 2016)
Administer or manage the forest is a very interesting activity and into the desire of many parties for fighting over. This is due to the forestry sector and the potential to bring a source of income. Conflicts of authority or claims that occur in the field of forestry for at least related to the legal instruments governing on division of authority. To prevent possible conflicts of authority in the field of forestry, need to be investigated and disclosed on the basic principles of authority. Resolving conflicts of authority and determine who has the most right to manage forests, not enough to simply rely on the creation of new rules, but must begin with the affirmation of principles law and “enforcement” law.